(untitled) (INNOVATIVE ECONOMY, 2024)
Krupskyi O.P., Stasiuk Yu.M., Huk O.O. IMPROVING BUSINESS EFFICIENCY IN COSMETOLOGY INSTITUTIONS Purpose. The aim of the article is to develop recommendations for improving business efficiency in cosmetology institutions through the introduction of modern management approaches and technologies. Methodology of research. The study was conducted using a comprehensive approach that included both quantitative and qualitative research methods. In particular, the analysis of statistical data was used to assess the market of cosmetology services and its dynamics, which allowed us to identify key trends and performance indicators of institutions. Surveys of experts in the field of cosmetology and management were used to collect opinions on the implementation of modern management practices and digital technologies in cosmetology institutions. Case studies of cosmetology institutions were conducted to analyse real-life examples of the implementation of automation systems, artificial intelligence and marketing tools, which allowed us to identify the most successful practices and assess their impact on increasing profitability and competitiveness. Findings. It was found that the main factors affecting the efficiency of cosmetology institutions are innovative management practices, effective use of digital technologies and adaptation to new marketing trends. It has been established that the introduction of business process automation systems, improvement of marketing strategies and the use of artificial intelligence can significantly increase the profitability and competitiveness of institutions. Originality. The results of the study have introduced new aspects to the understanding of management practices in the cosmetology business, in particular, effective strategies for implementing digital technologies and marketing tools have been identified. The importance of artificial intelligence in optimizing business processes and improving customer interaction is shown. Practical value. The practical recommendations developed in the study can be used by cosmetology institutions to improve the efficiency of their activities. The recommendations include the introduction of modern management practices, digital tools and adaptation to new marketing trends, which will allow institutions to increase their competitiveness and profitability. Key words: cosmetology institutions, management practices, digital technologies, marketing strategies, business efficiency, artificial intelligence.